An Outbreak of Coxsackievirus B Type 2 Acute Meningoencephalitis in Children, Israel, July–September 2022. Issue 5 (14th February 2023) - Kriger, Or; Abramovich, Alon; Fratty, Ilana S.; Leshem, Eyal; Amit, Sharon; Stein, Michal; Ben-Zeev, Bruria; Via-Dorembus, Sara; Hoffmann, Chen; Rabinowicz, Shira; Weil, Merav
Abstract : During July–September 2022, 14 children suffering from meningoencephalitis tested positive for Coxsackievirus B2 (8 cerebrospinal fluid, 9 stool samples). Mean age 22 months (range 0–60 months); 8 were males. Seven of the children presented with ataxia and 2 had imaging features of rhombencephalitis, not previously described in association with Coxsackievirus B2.